2017
DOI: 10.3389/fnins.2017.00499
|View full text |Cite
|
Sign up to set email alerts
|

Concurrence of Inappropriate Antidiuretic Hormone Secretion and Cerebral Salt Wasting Syndromes after Traumatic Brain Injury

Abstract: Syndrome of inappropriate antidiuretic hormone (SIADH) and cerebral salt wasting syndrome (CSWS) as the two most common neuroendocrine diseases, have been recognized and understood by many neurologists. Although SIADH and CSWS are the common causes of central hyponatremia after traumatic brain injury (TBI), a few cases are mixed, with the coexistence of the two pathological pathomechanism. However, the mixed type of both SIADH and CSWS has not been clearly reported in any literature. Here, we present the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
(47 reference statements)
0
8
0
3
Order By: Relevance
“…So, there is a theoretical possibility as well as studies also to support that sometimes they both coexist in the same patient wherein the cause is labelled as mixed. Possibly, miscellaneous causes of hyponatremia in a few previous studies as summarized here might have included mixed cases too 1,2 . I suggest little elaboration of the mixed cause and strategy of its management should have been included as well.…”
Section: Open Peer Reviewmentioning
confidence: 91%
See 1 more Smart Citation
“…So, there is a theoretical possibility as well as studies also to support that sometimes they both coexist in the same patient wherein the cause is labelled as mixed. Possibly, miscellaneous causes of hyponatremia in a few previous studies as summarized here might have included mixed cases too 1,2 . I suggest little elaboration of the mixed cause and strategy of its management should have been included as well.…”
Section: Open Peer Reviewmentioning
confidence: 91%
“…Hyponatremia is a disorder of water balance. The severity of hyponatremia has been categorized as mild (130-134mEq/L), moderate (120-129 mEq/L) and severe (<120 mEq/L) 2 , and serum sodium <125 mEq/L is regarded as an independent predictor of mortality, especially in critically ill patients;. In a review of hospitalized patients with hyponatremia, mortality increases by 1.5-60 times in the patients with hyponatremia compared to controls 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Leonard et al (2015) found the incidence of CSWS varies widely in TBI patients, from 0.8 to 34.6%. Nevertheless, a recent report by Shen et al (2017) presented the concurrent syndrome of SIADH and CSWS after TBIs in four patients, which poses to clinicians new ideas for the diagnosis and treatment of TBI-associated HN.…”
Section: The Incidence and Clinical Characteristics Of Siadh And Cswsmentioning
confidence: 99%
“…Furthermore, the incidence of the disorders varies, in which transient DI was the most reported disorder, followed by SIADH and CSWS [ 2 , 3 ]. Additionally, DI, SIADH, and CSWS have been reported concurrently after neurosurgery, especially pituitary gland surgeries and post-traumatic brain injury [ 2 , 4 , 5 ]. In this case report, we present a rare case of a patient with triphasic DI and CSWS, presenting after neurosurgery, and there were difficulties in differentiating the second phase of DI, which resembles SIADH, and CSWS.…”
Section: Introductionmentioning
confidence: 99%